Hajj Financial Management in the MaqÄá¹£id SharÄ«â€™ah Perspective - Alfiyanti, Ulfah; Firdaus, Achmad; Fatah, Dede Abdul (Al-Ahkam, 2019)
This paper analyzes the management of the pilgrimage fund to the concept of Islamic wealth management and the management of the pilgrimage fund and its compliance with the maqÄá¹£id al-sharÄ«'ah. The first is done by analyzing the management of hajj funds by BPKH on the management of Islamic wealth. The second is done through interviews with academics, regulators, experts and practitioners. Descriptive processing is done through Strategic Assumption Surfacing and Testing (SAST). The analysis is done by selecting the 'important' and 'definite' variables. The results showed that the determinants of Hajj fund management according to Islamic wealth management were contracts, zakat and transparency. Hajj fund management policies for the protection of religion, including the setting of a fair and transparent haj quota, building infrastructure facilities for the pilgrimage, ensuring terms and conditions Life protection through the use of halal vaccines, providing and funding Hajj monitors, improving catering, lodging, transportation and health services and providing congregational data to the Ministry of Health. Protection of reason through improving the quality of rituals. Protection of assets through transparency in the management of hajj funds, direct investment in harmony with sharia, and management of hajj funds in Islamic banking.